An improved TOPSIS-ANP composite shielding material performance evaluation method based on gray relational projection algorithm - Zhang, Kan; Liang, Xin; Wei, Hua; Liu, Sishi; Su, Kai (Frontiers in Energy Research, 2023)
The performance of shielding materials directly affects the radiation protection effect and plays a very important role in the process of ensuring the safety of nuclear energy. Therefore, this paper introduces the performance evaluation of composite shielding materials, which firstly points out the disadvantages of the traditional TOPSIS method, proposes a weighted projection model of composite shielding materials under extended TOPSIS theory, and clarifies the principle of projection dimensional reduction and algorithm implementation. Secondly, this paper also introduces the basic assumption of nonlinear mapping relationship between index dimensions, and scientifically determines the weight of index system based on ANP structural model, so as to form an improved TOPSIS-ANP composite shielding material performance evaluation method based on gray relational projection algorithm with coupling characteristics. The empirical results show that the improved TOPSIS-ANP composite shielding material evaluation method proposed in this paper is consistent with the conclusion of the ratio of lead-boron-polyethylene shielding materials optimized based on genetic algorithm, which proves the effectiveness of the evaluation method proposed in this paper. Meanwhile, the evaluation index system of this method is more comprehensive, and the evaluation method is more efficient and scientific as well, which has a good promotion prospects and application advantages.